Effects of Wuqinxi on blood pressure and lipids in hypertensive middle-aged and elderly adults: a meta-analysis - Tianhao Zhang; Mingang Guo; Tao Li; Zehui Zhang (Frontiers in Medicine, 2026)
Purpose This study aimed to quantify the therapeutic effects of standardized Wuqinxi exercise on blood pressure, lipid profile, and resting heart rate in middle-aged and older adults with primary hypertension, and to grade the evidence certainty using the GRADE framework. Methods We systematically searched Web of Science, Wanfang Data, CNKI, EBSCO, and PubMed (January 2000 to June 30, 2026) for randomized controlled trials (RCTs) evaluating Wuqinxi as an adjunctive intervention for hypertension. Eleven RCTs (770 participants, aged 30–80 years, 3–6 months duration) were included. Primary outcomes were changes in systolic blood pressure (SBP), diastolic blood pressure (DBP), high-density lipoprotein (HDL), and low-density lipoprotein (LDL). Meta-analyses were performed using random-effects models, with pre-specified sensitivity analyses excluding studies with high risk of bias, non-standard protocols, or incompatible controls. Results Wuqinxi significantly reduced SBP by 5.3 mmHg and DBP by 6.7 mmHg, improved HDL [standardized mean difference (SMD) = 0.71, 95% confidence interval (CI): 0.40–1.02], and reduced LDL (SMD = −0.63, 95% CI: −1.19 to −0.07). GRADE evidence quality was moderate for blood pressure, low for HDL, and very low for LDL. Conclusion Wuqinxi is a safe, low-cost adjunctive therapy for hypertension with consistent blood pressure-lowering effects over 3–6 months. We recommend integrating 5–6 sessions weekly into community and clinical hypertension care. Lipid benefits require confirmation through high-quality RCTs with standardized protocols. Systematic review registration PROSPERO, identifier CRD420261396941.